Impact of varying the phenylboronic acid position in macrocyclic Eu(iii) complexes on the recognition of adenosine monophosphate. Issue 20 (5th September 2022) - Bodman, Samantha E.; Breen, Colum; Plasser, Felix; Butler, Stephen J.
Abstract : We present a series of sterically demanding Eu(iii ) complexes and identify the optimal position of the peripheral phenylboronic acid to achieve the multisite recognition of AMP (adenosine monophosphate) in aqueous solution. Abstract : The selective recognition of anions in water by artificial receptors remains a significant research challenge. The creation of a receptor selective for adenosine monophosphate (AMP) is particularly difficult due to its similarity in structure with the more negatively charged anions, ADP and ATP. We recently developed a macrocyclic Eu(iii ) complex that selectively binds AMP in water, by incorporating a sterically demanding quinoline arm that inhibits coordination of commonly interfering anions such as ATP. A phenylboronic acid motif was installed within the ligand to engage the ribose sugar of AMP through reversible covalent bonds. Herein we report two new Eu(iii ) complexes, [Eu· o BOH2 ] + and [Eu· p BOH2 ] +, to investigate the impact of varying the position of the phenylboronic acid group on the anion binding properties of the Eu(iii ) receptors. We found that [Eu· p BOH2 ] + showed preferential binding to AMP over ATP, but exhibits a lower level of discrimination between AMP and ADP compared with the isomeric complex [Eu· m BOH2 ] + . Surprisingly, [Eu· o BOH2 ] + showed no response to anions but displayed a unique response to pH, ascribed to the direct coordination of the ortho -boronate ester to the Eu(iii ) centre. Finally, we present first principles computations that offer a promising approach to access the emission spectra of lanthanide complexes, aiding the design of responsive lanthanide probes with specific photophysical properties.